Sex-chromosome complement and Activin-A shape the therapeutic potential of TNFR2 activation in a model of MS and CNP - Shruti Gupta; Sreejita Arnab; Kayla L. Nguyen; Marisa Reed; Payam Fathi; Kelly Tammen; Emma Turner; Erin Jones; Roman Fischer; David Mendelowitz; John R. Bethea (Proceedings of the National Academy of Sciences, 2025)
Tumor necrosis factor receptor 2 (TNFR2) activation is a promising-therapeutic strategy for autoimmune disorders such as multiple sclerosis (MS) and chronic neuropathic pain (CNP). This study aimed to identify mechanisms governing the sex-specific efficacy of TNFR2 activation on abrogating pain and motor disease severity in mice experiencing experimental autoimmune encephalomyelitis (EAE), a rodent model of MS. We find that the XX sex-chromosome complement is indispensable for TNFR2-mediated attenuation of EAE-associated motor disease. Mice with XY chromosomes experienced exacerbated motor disease severity, associated with an elevated magnitude of neurodegeneration and demyelination. Contrasting this, we show that TNFR2-mediated alleviation of EAE induced CNP is both sex and sex-chromosome independent. However, the alleviation of CNP following TNFR2 activation across two different neuropathic pain models (EAE and chronic constriction injury) was dependent on the gonadal hormone Activin-A. This suggests a shared mechanism through which gonadal-derived factors impact TNFR2-mediated pain relief, independent of sex hormones. These findings highlight the importance of considering sex chromosomes and sex-independent gonadal hormones in evaluating potential sex-specific differences in drug efficacy during therapeutic development.